Conditions of human development in Wayuu child malnutrition - García Peña, John Jairo; Pimienta Arismendy, José Camilo (Revista Colombiana de Ciencias Sociales, 2026)
Objective: To analyze the incidence of factors associated with human development in Wayuu child malnutrition in the department of La Guajira, Colombia. Method: A qualitative study based on a social phenomenological methodology, using semi-structured interviews. Results: Wayuu lived experiences reveal a progressive conception of development, as well as the influence of the territorial context as a determining factor in child malnutrition. The findings show that this social scourge constitutes a multidimensional problem and represents the materialization of precarious living conditions and social inequality to which this community has historically been exposed. Conclusions: There is a need to implement comprehensive approaches that enable, through coordinated institutional actions, the effective participation of the community while recognizing and valuing their ancestral knowledge.the department of La Guajira. Method: Qualitative, phenomenological methodology, through semi-structured interview. Results: a conception of progressive development is found in the Wayuu experiences, and an incidence of the territorial context as a condition for child malnutrition. It is evident that this social scourge is a multidimensional problem, a materialization of precariousness and social inequality to which this community has historically been exposed. Conclusions: it is necessary to implement comprehensive proposals that enable, through articulated institutional actions, the effective participation of the community, recognizing their ancestral knowledge.